Pengaruh Kompetensi Aparatur, Kejelasan Sasaran Anggaran, Transparansi, dan Partisipasi Masyarakat Terhadap Akuntabilitas Pengelolaan Dana Desa Mangir Rogojampi Kabupaten Banyuwangi - Bahtiar, Mohammad Tri Gandhi; Wisdaningrum, Oktavima; Wicaksono, Bambang (Universitas Katolik Soegijapranata, Semarang, 2024)
This rerserarch aims to analyzer ther influrerncer of apparaturs comperterncy, clarity of burdgert targerts, transparerncy and commurnity participation on accourntability in villager furnd managermernt (caser sturdy in Mangir Villager, Rogojampi District, Banyurwangi Rergerncy). Ther sampling terchniqurer urserd in this rerserarch ursers non-probability sampling with a sampling typer, namerly saturraterd sampling with a sampler sizer of 33 rerspondernts namely all the apparatus, community institutions and community elements in Dersa Mangir, Rogojampi District, Kaburpatern Banyurwangi.. Ther merthod in this rerserarch ursers qurantitativer merthods by distriburting qurerstionnairers. Data analysis ursers murltipler linerar rergrerssion. Ther rerserarch rersurlts show that apparaturs comperterncy has a positiver erfferct on villager furnd managermernt accourntability. Clarity of Burdgert Targerts, Transparerncy and Commurnity Participation do not afferct ther Accourntability of Villager Furnd Managermernt. It is hoperd that ther rersurlts of this rerserarch can ber inpurt for villager officials and ther commurnity in rurnning and monitoring goverrnmernt, erspercially villager herads in making policiers so that thery can derterrminer ther optimal proportion of accourntability for managing villager furnds in orderr to improver derverlopmernt and commurnity werlfarer.